2018
DOI: 10.1080/09168451.2017.1399788
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of formononetin in ameliorating learning and memory impairment in mouse model of Alzheimer’s disease

Abstract: Alzheimer's disease (AD) is the most common cause of dementia among elderly population. Deranged β-amyloid (Aβ) trafficking across the blood-brain barrier is known to be a critical element in the pathogenesis of AD. In the vascular endothelial cells of hippocampus, Aβ transport is mainly mediated by low-density lipoprotein-associated protein 1 (LRP1) and the receptor for advanced glycation end (RAGE) products; therefore, LRP1 and RAGE endothelial cells are potential therapeutic targets for AD. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…BBB dysfunction can activate β and γ secretase and generate and increase Aβ level in AD (Cai et al, 2018). Aβ transport through BBB is regulated by low density lipoprotein-1 (LRP-1) and receptor for advanced glycation end products (RAGE) expressed on the surface of the endothelial cells (Fei et al, 2018). Loss of pericytes and astrocyte abnormalities increases Aβ level in AD brains.…”
Section: Stress and Alzheimer’s Diseasementioning
confidence: 99%
“…BBB dysfunction can activate β and γ secretase and generate and increase Aβ level in AD (Cai et al, 2018). Aβ transport through BBB is regulated by low density lipoprotein-1 (LRP-1) and receptor for advanced glycation end products (RAGE) expressed on the surface of the endothelial cells (Fei et al, 2018). Loss of pericytes and astrocyte abnormalities increases Aβ level in AD brains.…”
Section: Stress and Alzheimer’s Diseasementioning
confidence: 99%
“…FMT has a bioavailability of 21.8% and shows different absorption in all gastrointestinal segments ( Luo et al., 2018 ). An increasing body of evidence suggests that FMT exerts notable anti-inflammatory, anti-allergic, antioxidant, anti-hepatic steatosis, antiproliferative, and anticancer effects in vitro and animal models of many disease ( Wang et al., 2012 ; Xu and An, 2017 ; Fei et al., 2018 ; Li et al., 2018 ; Ong et al., 2019 ; Wang X. S. et al., 2019 ). Some reports demonstrate that FMT has neuroprotective effect in LPS-stimulated BV2 microglia and high-fat diet-induced cognitive disorder mice ( El-Bakoush and Olajide, 2018 ; Fu et al., 2019 ; Wang Y. et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that formononetin has beneficial therapeutic effects in several diseases, including cancer, diabetes, neurological disease, and cardiovascular disease [5,6]. Recently, the neuroprotective effect of formononetin in patients with AD has been demonstrated in both in vivo and in vitro studies [7,8]. However, the detailed molecular mechanisms for the pharmacological and biological actions of formononetin remain unknown.…”
Section: Introductionmentioning
confidence: 99%